mADP-RTs: versatile virulence factors from bacterial pathogens of plants and mammals - Wirthmueller, Lennart; Banfield, Mark J. (Frontiers in Plant Science, 2012)
Mono ADP-ribosyltransferases (mADP-RTs) are a family of enzymes that cleave NAD+ and covalently attach the ADP-ribosyl moiety to target proteins. mADP-RTs are well established as important virulence factors of bacteria that infect mammals. Cholera toxin, pertussis toxin, and diphtheria toxin are three of the best-known examples of mADP-RTs. They modify host target proteins in order to promote infection and/or killing of the host cell. Despite low sequence similarity at the primary amino acid level, mADP-RTs share a conserved core catalytic fold and structural biology has made important contributions to elucidating how mADP-RTs modify mammalian host targets. Recently, mADP-RTs were shown to be present in plant pathogenic bacteria, suggesting that mADP-RTs are also important virulence factors of plant pathogens. Crystal structures of plant pathogenic bacterial mADP-RTs are also now available. Here we review the structure/function of mADP-RTs from pathogens of mammals and plants, highlighting both commonalities and differences.